PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS (Studi Pada Perusahaan Farmasi yang Terdaftar di BEI Periode 2007-2011) - Sartika, Farahiyah; Herawati, Juni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of the efficiency of working capital (working capital turnover), liquidity (current ratio), and solvency (debt to total assets ratio) toward profitability (return on investment) either simultaneously or partially in the pharmaceutical company listed on the Indonesian Stock Exchange over period 2007-2011. Type of research used in this research is associative research that aims to explain the relationship between two or more variables through hypothesis testing. The sampling technique used was purposive sampling and obtained a sample of 7 companies. Data which have already collected are processed with classic assumption test before hypothesis test. To test the hypothesis proposed in this study used multiple regression analysis. The results of the research simultaneously using F test showed that all of the three independent variables have a significant effect on profitability (return on investment). The results of the research partially using t test showed that liquidity (current ratio) have positive significant influence on profitability (return on investment). While the efficiency of working capital (working capital turnover) and solvency (debt to total assets ratio) have no significant influence on profitability (return on investment). Keywords: Profitability, Efficiency of Working Capital, Liquidity, Solvency